EVALUASI ALIRAN PERMUKAAN, EROSI DAN SEDIMENTASI DI SUB DAS CISADANE HULU DENGAN MENGGUNAKAN MODEL AGNPS (AGRICULTURAL NON POINT SOURCE POLLUTION MODEL) - Sukandi Sukartaatmadja (Jurnal Keteknikan Pertanian, 2006)
ABSTRACT Composition of a good watershed management planning needs accurate information about erosion, runoff and its quality, so that its model for them, middle term and long term goal can be projected. The model had been used is AGNPS (agricultural non point source pollution model) is developed by Robert A. Young, Charles A. Onstad, David D. Bosch. And Wayne P. Anderson in 1987. The Objective of this reseacrh is to looked for the effect of soil conservation had been done with rehabilitation activities plan to watershed condition using AGNPS model wich is divided into two plans. The effect of soil conservation activieties by a better plan wich is suited with Upper Cisadane Watershed could decreased runoff volume, runoff peak rate, annual erosion and sediment weight into 20% so that it could repaired the condition of Upper Cisadane Watershed wich is dangerouse before. Keyword: AGNPS, runoff, erosion, sediment, soil conservation, plan Diterima: 9 Mei 2006; Disetujui: 30 Mei 2006